P107Role of plasma membrane-associated AKAPs 15/18 and 79 for the regulation of cardiac IK1 current by protein kinase A. (15th July 2014) - Seyler, C; Scherer, D; Koepple, C; Kulzer, M; Korkmaz, S; Thomas, D; Kaya, Z; Backs, J; Katus, HA; Zitron, E
Abstract: Background: The cardiac inwardly rectifying potassium current IK1 stabilises the diastolic resting membrane potential of ventricular cardiomyocytes. Protein kinase A (PKA) induces an inhibition of IK1 current which strongly promotes focal arrhythmogenesis under increased catecholamine levels. The molecular mechanisms underlying this regulation have only partially been elucidated to date. Furthermore, the role of A Kinase Anchoring Proteins (AKAPs) in this regulation has not been examined yet. The objective of this project was to elucidate the molecular mechanisms underlying the inhibition of IK1 by PKA and to identify novel molecular targets for antiarrhythmic therapy downstream β-adrenoreceptors. Methods: Cardiac IK1 current was measured in isolated rat ventricular cardiomyocytes using whole-cell patch clamp. Kir2.x channels and AKAPs were expressed in Xenopus oocytes and current recordings were performed using the double-electrode voltage-clamp technique. Association of channels and AKAPs was examined with the use of co-immunoprecipitation and immunofluorescent confocal microscopy in isolated cardiomyocytes and in mammalian cell lines. Results: In patch clamp experiments, activation of PKA inhibited IK1 current in rat ventricular cardiomyocytes. This regulation was markedly attenuated by disrupting PKA-binding to AKAPs with the peptide inhibitor AKAP-IS. In expression systems, we observed functional and spatial coupling of the plasma membrane-associated AKAP15/18 and AKAP79 to Kir2.1 and Kir2.2 channel subunits, but not to Kir2.3 channels, which underly IK1 currents. In contrast, AKAPyotiao had no functional effect on the PKA regulation of Kir channels. AKAP15/18 and AKAP79 co-immunoprecipitated with and co-localized to Kir2.1 and Kir2.2 channel subunits in ventricular cardiomyocytes. Conclusions: In this study, we provide evidence for the functional and spatial coupling of cardiac Kir2.1 and Kir2.2 subunits as molecular components of IK1 current with the plasma membrane-bound AKAPs 15/18 and 79. Cardiac membrane-associated AKAPs are a functionally essential part of the regulatory cascade determining IK1 current function and may be novel molecular targets for antiarrhythmic therapy downstream from β-adrenoreceptors.